Narrowband Raman fibre laser based on a dual-core optical fibre with FBGs inscribed by femtosecond radiation. (December 2018) - Skvortsov, M.I.; Abdullina, S.R.; Wolf, A.A.; Lobach, I.A.; Dostovalov, A.V.; Babin, S.A.
Abstract: The characteristics of Raman lasers based on a dual-core optical fibre are presented. Fibre Bragg gratings (FBGs), selectively inscribed in chosen cores by femtosecond radiation, are used as cavity mirrors. The laser configuration is optimised with respect to the output FBG reflectivity. The possibility of additional spectral filtering, based on the formation of a Michelson interferometer in the laser cavity by inscribing a pair of FBGs in different cores, is demonstrated.